(untitled) (Research, Society and Development, 2020)
Understanding cell balance and interference with proliferative fate makes the pentose phosphate pathway an essential target in metabolic processes. The objective of this work was to review the scientific journals for indications and reasons to block the pentose phosphate pathway as an alternative practice in the treatment of neoplasia. This review was developed from an exploratory review of articles selected in the database platforms of Latin American and Caribbean Literature in Health Sciences (Lilacs), and Scientific Eletronic Libray Online (SciELO), Medical Literature Analysis and Retrieval System Online (MedLine) and Google Scholar, whose documents are crucial to raise proposals that the theme aims at. The studies reviewed in this article, demonstrated positive results and of great importance for the activity of the pentose phosphate pathway. When thinking about metabolic reprogramming, we obtain a significant link related to cancer, and the mechanisms that cells use to support environments with intense energy needs and the involvement of PPP pathway activity, still need to be better understood, considering that, be positively regulated in cancer and become an attractive target in search of tumor prognosis and define new cancer treatments.